Inpatient medical management of severe pediatric obesity: Literature review and case reports - Goldman, Victoria E.; Espinoza, Juan C.; Vidmar, Alaina P. (Frontiers in Pediatrics, 2023)
Pediatric obesity rates continue to rise steeply with significant adverse effects on health outcomes across the lifespan. Significant obesity can affect the efficacy, side effects, and ability to use certain treatment, medication, or imaging modalities needed in the evaluation and management of acute pediatric conditions. Inpatient settings are rarely used as an opportunity for weight counseling and thus there is a paucity of clinical guidelines on how to manage severe obesity in the inpatient setting. We present a literature review and three patient cases with single-center protocol for non-surgical management of severe obesity in children admitted for other acute medical reasons. We performed a PubMed review from January 2002 to February 2022 utilizing keywords: “inpatient,” “obesity,” and “intervention.” For our cases, we identified three patients with severe obesity acutely impacting their health while admitted for medical treatment who concurrently underwent acute, inpatient, weight loss regimens at a single children’s hospital. The literature search yielded 33 articles describing inpatient weight loss treatments. Three patients met case criteria, all three of which demonstrated a decrease in their weight in excess percent of the 95th percentile after inpatient weight-management protocol implementation (% reduction BMIp95: 16-30%) This highlights obesity acutely limits or impacts specific medical care required during inpatient admissions in pediatric patients. It also suggests that implementation of an inpatient weight-management protocol during admission may provide an opportune setting to support acute weight loss and overall improved health outcomes in this high-risk cohort.